Perceptions of a peaceful death among Indonesian muslim nurses: A qualitative study - Akbar, M Agung (Indonesian Journal of Health Services, 2025)
Background: Nurses, as frontline healthcare providers, play a pivotal role in shaping patients’ end-of-life experiences. In Indonesia, where Islam is the predominant religion, nurses’ perceptions of a peaceful death are closely intertwined with religious and cultural values. However, empirical evidence exploring peaceful death from the perspective of Indonesian Muslim nurses remains limited. Objective: This study aimed to explore in depth the perceptions of a peaceful death among Indonesian Muslim nurses within the context of end-of-life care. Methods: This study employed a qualitative exploratory descriptive design. Participants were Muslim nurses with experience in caring for terminally ill patients and were recruited using purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis. Trustworthiness was ensured through credibility, dependability, confirmability, and transferability strategies. Results: Four main themes emerged from the data analysis: (1) acceptance of death as a divine decree, (2) peaceful death as freedom from unnecessary suffering, (3) the central role of family and interpersonal relationships, and (4) the professional role of nurses in facilitating a dignified death. These themes illustrate that a peaceful death is perceived as an integration of spiritual, physical, emotional, relational, and professional dimensions of care. Conclusion: Indonesian Muslim nurses perceive a peaceful death as a holistic process emphasizing spiritual acceptance, patient comfort, family support, and dignified nursing care. These findings highlight the importance of culturally and spiritually sensitive palliative nursing practices.